Employees' perceptions of the implementation of Akhlak values at PT Pegadaian - Antoni Ludfi Arifin; Taufan Maulamin; Resista Vikaliana; Rully Yusuf (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
PT Pegadaian officially internalizes PT Pegadaian Personnel with CHARACTERISTICS who uphold the values of Trust, Competence, Harmonious, Loyal, Adaptive and Collaborative, as standards of ethical values that serve as guidelines in working culture in realizing the spirit of BUMN for Indonesia.Ethics is important because it fulfills a basic human need when every employee wants to be and work for a fair and ethical organization. An organization perceived to be motivated by AKHLAK values is respected even by people in society who may have little understanding of the job and the business or organization. Its employees also respect values-driven organizations. This is a typical human resource on a network that places workers and decision makers. In addition, an organization driven by ethics and values is long term efficient. The sample used is the employees of PT Pegadaian as many as 200 samples. The results show that the indicators of AKHLAK values regarding work perfection, cooperation, human values of honesty and focus on customers based on the perception of pawnshop employees show good results. With AKHLAK values, it is hoped that it can improve the quality of employees so that it has an impact on the quality of employees' work.